1995
DOI: 10.1095/biolreprod53.3.732
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Interferon-τ Regulates Expression of Endometrial Receptors for Estrogen and Oxytocin but not Progesterone1

Abstract: Ovine interferon-tau (oIFN-tau) may stabilize endometrial progesterone receptor (PR) and/or inhibit estrogen receptor (ER) gene expression during pregnancy recognition to suppress endometrial oxytocin receptor (OTR) formation and production of luteolytic prostaglandin (PG) F2 alpha pulses. This study determined whether or not oIFN-tau stabilized PR expression in the endometrium during PR down-regulation by continuous exposure to progesterone. Twenty cyclic ewes were bilaterally ovariectomized and fitted with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
1
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 54 publications
8
79
1
3
Order By: Relevance
“…Proteins were prepared for IU injection as described previously (Spencer et al 1999b). This regimen of P4 and IFNT mimics the effects of P4 and the conceptus on endometrial expression of hormone receptors and IFNT-stimulated genes during early pregnancy in ewes (Spencer et al 1995, Kim et al 2003. All ewes were hysterectomized on day 17.…”
Section: Studymentioning
confidence: 99%
“…Proteins were prepared for IU injection as described previously (Spencer et al 1999b). This regimen of P4 and IFNT mimics the effects of P4 and the conceptus on endometrial expression of hormone receptors and IFNT-stimulated genes during early pregnancy in ewes (Spencer et al 1995, Kim et al 2003. All ewes were hysterectomized on day 17.…”
Section: Studymentioning
confidence: 99%
“…However, IFNτ does not prevent down-regulation of progesterone receptor levels that resulted from continuous injections of progesterone [57,60], but suppressed the estrogeninduced ER and OTR gene expression [61]. Therefore, the antiluteolytic effect exhibited by IFNτ in the endometrium is due to IFNτ preventing ER expression and subsequently estrogen-induced OTR expression [60,61].…”
Section: Biological Properties Of Ifnτ τ τ τmentioning
confidence: 99%
“…Intra-uterine injection of IFNτ causes the downregulation of OTR, ER and oxytocin-induced PGF2α production [55][56][57][58][59]. However, IFNτ does not prevent down-regulation of progesterone receptor levels that resulted from continuous injections of progesterone [57,60], but suppressed the estrogeninduced ER and OTR gene expression [61].…”
Section: Biological Properties Of Ifnτ τ τ τmentioning
confidence: 99%
“…It acts in a paracrine manner on the endometrium to establish and maintain pregnancy by suppressing the normal pattern of pulsatile release of uterine PFG 2α leading to luteolysis at the end of the estrous cycle. Several studies in the ewe have shown that IFNτ suppresses cyclic increases of the estrogen receptor gene transcription and thereby prevents estrogen induced increases in oxytocin receptor gene expression, which normally occurs in cyclic ewes undergoing luteolysis (Knickerbocker et al, 1986;Spencer et al, 1995).…”
Section: Maternal Recognition Of Pregnancy and The Pivotal Role Of Ifmentioning
confidence: 99%
“…Even though one may assume, IFNτ does not act to stabilize or prevent autologous downregulation of the progesterone receptor mRNA and protein expression in the endometrium, which normally occurs towards the end of the estrous cycle (Spencer et al, 1995).…”
Section: Maternal Recognition Of Pregnancy and The Pivotal Role Of Ifmentioning
confidence: 99%